Two-layer iterative energy dispatch for a multi-energy-flow VPP in the distribution power grid - Li, Wanbin; Zhou, Zaiyan; Zhang, Yuqi; Jin, Guiyue; Wang, Wenxin; Ren, Yanchao; Wan, Yuchao; Liu, Yimin; Liu, Chunxiu (Frontiers in Energy Research, 2024)
In light of the growing urgency surrounding energy and environmental concerns, this paper presents a two-layer iterative energy dispatch strategy tailored for a multi-energy-flow virtual power plant (VPP) operating within the distribution power grid. The proposed strategy unfolds in two key phases. Firstly, it establishes an energy dispatch framework designed specifically for the multi-energy-flow VPP within the distribution power grid. Subsequently, it introduces an improved ant colony algorithm aimed at optimizing the output power of each VPP. In addition, the paper presents an optimization method for substation energy dispatch. This method utilizes a delay-aware consensus algorithm with the substation dispatch cost increment rate as the consensus variable, taking into account the communication delay between VPPs. Integrating a proportional-derivative (PD) control mechanism enhances the convergence speed of the delayaware consensus algorithm and enables real-time energy dispatch of the multi-energy flow VPP.The paper concludes by validating the efficacy of the proposed approach through simulation, thereby addressing the challenges and adapting to the shifting energy and environmental landscape.